Oncologic impact of delay between diagnosis and radical nephroureterectomy - Wu, Kuan-Hsien; Chang, Chao-Hsiang; Wu, Hsi-Chin; Huang, Steven K.; Liu, Chien-Liang; Yang, Cheng-Kuang; Li, Jian-Ri; Tseng, Jen-Shu; Lin, Wun-Rong; Yu, Chih-Chin; Lo, Chi-Wen; Huang, Chao-Yuan; et al. (Frontiers in Oncology, 2022)
Purpose This study aimed to evaluate the oncological outcome of delayed surgical wait time from the diagnosis of upper tract urothelial carcinoma (UTUC) to radical nephroureterectomy (RNU). Methods In this multicenter retrospective study, medical records were collected between 1988 and 2021 from 18 participating Taiwanese hospitals under the Taiwan UTUC Collaboration Group. Patients were dichotomized into the early (≤90 days) and late (>90 days) surgical wait-time groups. Overall survival, disease-free survival, and bladder recurrence-free survival were calculated using the Kaplan–Meier method and multivariate Cox regression analysis. Multivariate analysis was performed using stepwise linear regression. Results Of the 1251 patients, 1181 (94.4%) were classifed into the early surgical wait-time group and 70 (5.6%) into the late surgical wait-time group. The median surgical wait time was 21 days, and the median follow-up was 59.5 months. Our study showed delay-time more than 90 days appeared to be associated with worse overall survival (hazard ratio [HR] 1.974, 95% confidence interval [CI] 1.166−3.343, p = 0.011), and disease-free survival (HR 1.997, 95% CI 1.137−3.507, p = 0.016). This remained as an independent prognostic factor after other confounding factors were adjusted. Age, ECOG performance status, Charlson Comorbidity Index (CCI), surgical margin, tumor location and adjuvant systemic therapy were independent prognostic factors for overall survival. Tumor location and adjuvant systemic therapy were also independent prognostic factors for disease-free survival. Conclusions For patients with UTUC undergoing RNU, the surgical wait time should be minimized to less than 90 days. Prolonged delay times may be associated with poor overall and disease-free survival.